Trump: how did he happen and what will he do - Lachmann, Richard (2017)
This article identifies the long-term bases of Republican electoral dominance. It then highlights the specific factors that allowed Trump to win in 2016. Third, it enumerates the policies that Trump and Congressional Republicans will be able to implement because they control the Federal government. Finally, it discusses the opportunities for opposition to Trump and speculates on the likelihood that those efforts will be successful and how unanticipated events might strengthen or undermine Republican power.